2002
DOI: 10.1080/03014223.2002.9517712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plant microfossils in prehistoric coprolites from Harataonga Bay, Great Barrier Island, New Zealand

Abstract: We show results of palynological and phytolith analysis of coprolites from Harataonga Bay, Great Barrier Island. Because human and dog diets may overlap considerably, the microfossil evidence does not with certainty indicate which of these two species deposited them. The coprolites give insights into prehistoric Maori agriculture, gathering of wild plants, diet, and time of year of site occupation. Gourd (Lagenaria siceraria) pollen found in the coprolites shows that this exotic cultigen was being cultivated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The second most common microscopic component identified in coprolite studies are ova and other evidence of parasites Dittmar and Steyn 2004;Evans et al 1996;Fry and Moore 1969;Fugassa et al 2006;Horrocks et al 2004;Jouy-Avantin et al 1999;Ortega and Bonavia 2003;Shin et al 2009;Toker et al 2005). To date, little attention has been focused on the identification of phytoliths and starch granules from coprolites, although there are some exceptions (Danielson and Reinhard 1998;Horrocks et al 2003;Horrocks et al 2004;Horrocks et al 2002;Reinhard 2006;Reinhard and Danielson 2005). Analysis of these microscopic components provides corollary lines of evidence to interpretations based on the macroscopic and aDNAcomponents.…”
Section: Macroscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common microscopic component identified in coprolite studies are ova and other evidence of parasites Dittmar and Steyn 2004;Evans et al 1996;Fry and Moore 1969;Fugassa et al 2006;Horrocks et al 2004;Jouy-Avantin et al 1999;Ortega and Bonavia 2003;Shin et al 2009;Toker et al 2005). To date, little attention has been focused on the identification of phytoliths and starch granules from coprolites, although there are some exceptions (Danielson and Reinhard 1998;Horrocks et al 2003;Horrocks et al 2004;Horrocks et al 2002;Reinhard 2006;Reinhard and Danielson 2005). Analysis of these microscopic components provides corollary lines of evidence to interpretations based on the macroscopic and aDNAcomponents.…”
Section: Macroscopic Analysismentioning
confidence: 99%
“…Analysis of the microscopic fraction of specimens is an important part of coprolite studies. Most of this work has focused on the identification of pollen grains, which can inform on diet, seasonality of deposition, and medical practices (Carrion et al 2005;Carrion et al 2001; Dean 1993Dean , 2006Horrocks et al 2003;Horrocks et al 2004;Horrocks et al 2002;Kelso and Solomon 2006;Reinhard et al 2006;Reinhard et al 1991;Riskind 1970;Sobolik 1988a). The second most common microscopic component identified in coprolite studies are ova and other evidence of parasites Dittmar and Steyn 2004;Evans et al 1996;Fry and Moore 1969;Fugassa et al 2006;Horrocks et al 2004;Jouy-Avantin et al 1999;Ortega and Bonavia 2003;Shin et al 2009;Toker et al 2005).…”
Section: Macroscopic Analysismentioning
confidence: 99%
“…To date, most starch research has focused on tools and soils recovered from the Tropics, with very little focus on the potential of this line of research in temperate climates (Fullagar and Field 1997;Fullagar et al 2006;Fullagar et al 1996;Fullagar et al 1998;Horrocks et al 2004;Horrocks et al 2002;Horrocks and Lawlor 2006;Horrocks and Nunn 2007;Horrocks and Weisler 2006;Irwin et al 2004;Lentfer et al 2002;Pearsall et al 2004;Perry 2004a, b, AmaTerra Environmental, Inc. 2005Perry et al 2007;Piperno 1998;Piperno and Holst 1998;Piperno et al 2004;Smith et al 2001). A handful of temperate Old World sites have been investigated.…”
Section: Starch In Archaeologymentioning
confidence: 99%
“…This effect would be intensified given the low stature of L. siceraria. Horrocks et al (2002) have identified L. siceraria pollen from dog or human coprolites of around AD 1300-1600 (NZA-12591) buried in a beach dune on Great Barrier Island in the Hauraki Gulf, New Zealand. These data suggest direct consumption of flowers, but might also reflect consumption of residues on young L. siceraria, or even inadvertent ingestion during hand pollination (Horrocks 2004).…”
Section: Introduced Plantsmentioning
confidence: 99%